Strategi Propaganda dalam Iklan Kampanye Anies Baswedan dan Cak Imin : Analisis Wacana pada Pemilu Presiden dan Wakil Presiden 2024 - Dela Afyani; Arfian Suryasuciramdhan; Siti Fadilah; Nur Fadilah; Desti Aprilyani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This analysis discusses the political communication strategy of presidential and vice presidential candidate pair Anies Baswedan and Muhaimin Iskandar (Cak Imin) in the 2024 Presidential Election through a discourse analysis of their campaign advertisements. This campaign utilizes various propaganda techniques such as glittering generalities, plain folks, transfer, and contrast framing to shape political images, strengthen emotional connections with voters, and implicitly criticize political opponents. Symbols of the people and religiosity are used strategically to create social identification and legitimacy in the eyes of the public, especially traditional Muslim voters. In addition, the strategy of political public relations and the use of social media, including TikTok Live, show how the modern campaign approach has shifted towards digitalization and more targeted message segmentation. This analysis underlines the importance of emotional, symbolic, and inclusive communication narratives to avoid social fragmentation and shows that contemporary political campaigns are not only about conveying information, but also about strategic symbolic influence and imaging in the digital era.